Opinion of the University Teachers Towards Educational Television Programmes - Jayakumar, R. (American Journal of Education and Learning, 2016)
The technology of instructional television is dynamic. It is improving and hopefully it is here to say. Universities and college teachers will never be able to claim that they really care about the learning process until professors and administrators are required to exhibit knowledge and proficiency in the teaching process including the ability to use instructional television. Even though the University teachers have expressed their opinion about Educational Television programmes, many of the University teachers are not in the habit of viewing ETV programmes. Hence the University authorities or the U.G.C. may take initiative to see that the University teachers developed a tendency to view the ETV programmes and make use of it.